VERBA BERARGUMEN KHUSUS DALAM BAHASA INDONESIA - Deni Karsana (Multilingual, 2013)
The unity of the element sentence is important. The good sentence structure has complete  elements, especially the two elements that are subject and predicate. The predicate is mostly constructed by Verbs. This fact made Verbs have the important function in a sentence. The method applied in this research are qualitative descriptive. The result shows that there is special argument ofVerbs in Indonesian.